Innovative teaching methods. Effective solutions to complex contests - Panciroli, Chiara; Corazza, Laura; Vignola, Patrizio; Marcato, Elena; Leone, Daniela (Form@re - Open Journal per la formazione in rete, 2018)
Innovative teaching methods can be thought of as a complex device, where cognitive, emotional and procedural elements are interconnected. Teaching is also defined as innovative when it is possible to find successful and effective solutions to complex contests in terms of mediation and sustainability. This abstract investigates three different teaching methods (Flipped Classroom, Cooperative Learning and Project Based Learning) and the complex system of Competency-based Learning they refer to. Furthermore, not only does it examine three experiences and highlight their strengths and weaknesses (according to the SWOT analysis), but also provides recommendations for limiting risks and making use of the exploiting opportunities. Didattica innovativa. Soluzioni efficaci per contesti complessi La didattica innovativa può essere intesa come dispositivo complesso, in cui interagiscono elementi cognitivi, affettivi e procedurali. La didattica si definisce innovativa, inoltre, quando sa creare una dialettica tra complessità del contesto e soluzioni metodologiche efficaci, sia in termini di mediazione, sia di sostenibilità dei processi. L’articolo prende in esame tre strategie d’insegnamento (flipped classroom, cooperative learning, Project Based Learning) e il relativo sistema complesso della didattica per competenze e analizza tre esperienze d’insegnamento, evidenziandone gli elementi di forza e di debolezza e le relative raccomandazioni per limitare i rischi e sfruttare le opportunità.